Identification of Phytochemicals of Phoenix dactylifera L. Cv Ajwa with UHPLC-ESI-QTOF-MS/MS - Omaima Adil Najm; Mohamed Adel Elkadi; Wan Omar Bin Abdullah; Amin Ismail; Faizul Helmi Addnan; Nur Fariha Mohd Manzor; Fadlul Azim Fauzi Mansur (Taylor and Francis Ltd., 2024)
Indexed by WOS/ Scopus